Impact of Succinylcholine vs. Rocuronium on Apnea Duration for Rapid Sequence Induction: A Prospective Cohort Study - Tang, Lijun; Zhao, Xiao; Li, Shitong; Huang, Lina; Li, Jinbao; Chen, Lianhua; Huang, Shiwei (Frontiers in Medicine, 2022)
To compare the apnea time in patients treated with 1.5 mg/kg succinylcholine, 1.0 mg/kg succinylcholine, or 1.2 mg/kg rocuronium. This is a prospective cohort study, conducted in the Department of Anesthesiology in Shanghai General Hospital from July 2020 to November 2020. Patients who underwent elective surgery requiring rapid sequence induction intubation (RSII) were enrolled. Apnea time was defined as the time from apnea prompted by the PETCO2 waveform to the time the point of oxygen saturation declined to 90% (T90) and 95% (T95) after succinylcholine or rocuronium administration. The primary outcome was T90 and T95 in different succinylcholine-dose groups (1.5 mg/kg versus 1.0 mg/kg) and different relaxant groups: succinylcholine (1.5 mg/kg) versus rocuronium (1.2 mg/kg). The data of a total number of 265 participants were subjected to final analysis. The succinylcholine (1.0 mg/kg) group had a significantly longer T90 (56.84, 95% confidence interval [CI, 16.24-97.44], P = 0.015) and T95 (48.09, 95% CI [7.11, 89.07], P = 0.003) than the succinylcholine (1.5 mg/kg) group. In addition, significantly longer T90 (50.57, 95% CI [12.58, 88.57], P = 0.003) and T95 (48.09, 95% CI [7.11, 89.07], P = 0.012) were observed in the rocuronium (1.2 mg/kg) group than those in the succinylcholine (1.5 mg/kg) group). However, the T90 and T95 values were comparable between the succinylcholine (1.0 mg/kg) and rocuronium (1.2 mg/kg) groups. No severe side effects were observed. Rocuronium and the lower dose of succinylcholine showed longer T90 and T95 during RSII.